(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
The wide range of folk beliefs encompass many rituals. This study talks about Delikli Tash (Kamnik Canyon), i.e. one of the beliefs of the Yuruks living in Eastern Macedonia and the rituals that are performed there. During our research, we noticed that there are many rituals that need to be discovered and that are related to the beliefs in the Eastern Macedonian nomadic culture. This study discusses a stream that is a two-hour walk from the village of Kurfalija in Stip and an hour-long walk from the village of Gaber, as well as some of the rituals performed at this stream. Humans, by nature, feel the need to believe and pay obeisance to the supernatural. Within this belief, we see that man sometimes makes sacrifices to draw closer to God spiritually, and sometimes makes a vow to make his prayer come true. Man is a helpless creature before the supernatural forces, so what he has seen and heard and believed to be true he incorporates into the rituals he performs in order to follow the path of his ancestors. In this context, the rite of sacrifice appears in different forms in different nations. The paper mentions the customs and rituals of the people who came to Delikli Tash and offered sacrifices in case vows (promises) were made. Keywords: Nomads, folk beliefs, Delikli Tash, Eastern Macedonia, rite.